Understanding phosphorus dynamics and uptake in diverse soils of Indo-Gangetic Plains of India - K. K. Rao; Mandira Barman; Debarup Das; Vinod Kumar Sharma; Debrup Ghosh; H. Krishna; T. K. Das (PLoS ONE, 2025)
Phosphorus (P) is a critical macronutrient governing crop productivity, yet its availability in soils is limited by soil physico-chemical properties and interactions with other nutrients. The present study investigated phosphorus dynamics and uptake by wheat grown on twenty-five soils collected from different locations across the Indo-Gangetic Plains (IGP) of India. The soils exhibited wide variation in texture, pH (4.3–9.1), organic carbon (0.14–0.9%), and available macro and micro nutrients. Phosphate ion concentration and phosphate potential varied significantly (p < 0.05), reflecting contrasting P-supplying capacities. A pot experiment was conducted with wheat under control (no P) and 100% recommended P fertilizer application. Significant variation (p < 0.05) was observed in dry matter yield, P concentration, and P uptake among soils and treatments. Fertilizer P application enhanced dry matter accumulation by 10–70% depending on the soil, and P uptake increased more than twice in responsive soils. Particularly, P fertilization altered Zn concentration and the P/Zn ratio in wheat straw, indicating nutrient interactions. The results highlight that soil variability across the IGP governs P availability and wheat response, with implications for site-specific nutrient management to enhance productivity and minimize P-use inefficiencies.